Preparation method and application of hydrogen-bond-containing multi-dimensional composite material MXene (at) CE
By introducing polar hydrogen bonding into the MXene@CE composite, the problem of low gas transfer efficiency due to small layer spacing between two-dimensional materials is solved, and more efficient gas separation performance is achieved, especially in CO2/CH4 gas separation, which shows excellent performance.
Patent Information
- Application Number
- CN202411948816.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
Existing two-dimensional materials such as MXene in membrane separation have small layers due to nanosheet stacking, which limits the transfer efficiency of gas molecules, especially in CO2 separation.
By introducing polar hydrogen bonding into the MXene@CE composite material, the layer spacing of the two-dimensional nanosheets is increased, forming a wider gas transfer channel, and improving the gas separation efficiency of the membrane.
It significantly improves the gas separation efficiency, enhances the stability of the membrane, and shows excellent performance in CO2/CH4 gas separation, reaching the 2008 Robeson upper limit.
Smart Images

Figure HDA0005214364240000011 
Figure HDA0005214364240000012 
Figure HDA0005214364240000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mixed matrix membrane material preparation, and in particular to a preparation method of a hydrogen-bonded multidimensional composite material MXene@CE and its application in CO2 capture. Background Art
[0002] CO2 gas is a greenhouse gas that causes global warming. CO2 discharged into the atmosphere is mainly caused by the combustion of fossil fuels, and the flue gas emitted by fossil fuel power plants is the main source of CO2 emissions. At the same time, CO2 is widely present in fuel gases such as natural gas and bio-fermentation gas. The presence of CO2 not only reduces the purity of fuel gas, but also combines with moisture in the pipeline under low temperature conditions during the transportation of natural gas to form acidic gas that seriously corrodes the transportation pipeline. Therefore, it is urgent to develop efficient CO2 separation technology, which is of great significance to effectively reduce greenhouse gas emissions and purify energy gases.
[0003] Among the common CO2 separation methods, membrane separation is considered to be one of the most promising CO2 separation technologies due to its advantages of high efficiency, low energy consumption and low cost. The core of membrane separation is membrane materials. Common CO2 separation membranes include three categories: organic membranes, inorganic membranes and mixed matrix membranes. Mixed matrix membranes (Mixed matrix membranes, MMMs) are blended by dispersed fillers and continuous polymer matrices. Compared with traditional organic membranes and inorganic membranes, MMMs combine the advantages of organic membranes and inorganic membrane materials. They are a new type of membrane material with the potential to overcome the trade-off effect and exceed the Robeson upper limit.
[0004] At present, commonly used two-dimensional materials such as MXene face an important problem in membrane separation: the interlayer spacing of its nanosheets is small due to stacking, which limits the transfer efficiency of gas molecules, especially CO2 molecules, in the membrane. The insufficient interlayer spacing makes it difficult for gas molecules to pass quickly, thus affecting the separation performance of the membrane. . There are no reports on the application of MXene@CE, a multidimensional composite material containing hydrogen bonds that can effectively improve gas separation performance, in CO2 separation technology. Summary of the invention
[0005] In order to solve this problem, the present invention successfully increases the interlayer spacing of two-dimensional nanosheets by introducing polar hydrogen bonding into the MXene@CE composite material. Hydrogen bonding forms a polar environment between MXene nanosheets, significantly improving the interlayer spacing and the size of the gas transfer channel and creating a polar environment, thereby improving the gas separation efficiency of the membrane, especially showing higher performance in CO2 separation. Its inherent hydroxyl function produces hydrogen bonding with the polymer, thereby reducing the generation of interface defects and improving gas separation performance for application in CO2 capture. In order to achieve the above-mentioned purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a specific embodiment, the present invention provides a method for preparing a hydrogen-bonded multidimensional composite material MXene@CE, wherein the method comprises the steps of:
[0007] The method comprises the following steps:
[0008] (1) Lithium fluoride (LiF) is dispersed in a Teflon beaker containing hydrochloric acid (HCL) and deionized water to form a suspension A. Ti3AlC2 precursor is slowly added to the suspension A to form a suspension B. The suspension B is stirred and reacted under heating conditions, cooled to room temperature and centrifuged to obtain a suspension C.
[0009] (2) The suspension C prepared in step (1) is placed in a washing bottle for nitrogen protection. After ice bath ultrasound, the product is collected and centrifuged at low temperature. After repeated washing with hydrochloric acid and deionized water, it is freeze-dried to obtain single-layer and few-layer MXene.
[0010] (3) Add cellulose (CE) to deionized water, sonicate and stir to obtain a uniformly dispersed suspension D. Mix step (2) and suspension D in proportion, stir and sonicate until uniformly dispersed to form suspension E. Place suspension E in a petri dish and freeze-dry to obtain MXene@CE.
[0011] Furthermore, the amount of lithium fluoride (LiF), hydrochloric acid (HCl) and deionized water in step (1) is in the following relationship: 1 g: 15 mL: 5 mL; the amount of the Ti3AlC2 precursor and the suspension A prepared in step (1) is in the following relationship: 1 g: 20 mL, and the suspension B is a reaction system composed of lithium fluoride and hydrochloric acid solution. The suspension B is heated and stirred at a stirring speed of 500 rpm, reacted at 4 to 60°C for 2 to 8 hours, cooled to room temperature and centrifuged at a centrifugal speed of 6500 to 8000 rpm for 5 to 10 minutes to obtain a suspension C.
[0012] The nitrogen protection conditions described in step (2) are: transferring the suspension C to a washing bottle, performing ultrasonic treatment under nitrogen protection, the ultrasonic temperature is 0°C to 10°C, and the ultrasonic treatment time is 50 to 150 mins; after ultrasonication, repeatedly centrifuging at low temperature, the centrifugal speed is 3000 to 4000 rpm, the time is 1 to 20 mins, repeatedly washing with deionized water and hydrochloric acid until the pH is > 6, and then freeze-drying for 24 to 48 hours to obtain a single layer or a few layers of MXene.
[0013] The amount of cellulose (CE) described in step (3) is 5 g, and the amount of deionized water described in step (3) is 100 mL. The cellulose is dissolved and ultrasonically treated. The ultrasonic time is 20 to 30 mins and the stirring speed is 400 rpm to 500 rpm to obtain a uniformly dispersed suspension D. The mixing ratio of the MXene product and the cellulose suspension D described in step (2) is: the mass ratio of the MXene product to the suspension D is 1:5. After mixing, stir and ultrasonically treat. The ultrasonic time is 50 to 80 mins and the stirring speed is 400 rpm to 500 rpm until it is uniformly dispersed to form a suspension E. The suspension E is placed in a culture dish and freeze-dried for 24 to 48 hours to obtain a MXene@CE composite material.
[0014] In a specific embodiment, the present invention also provides a hydrogen-bonded multidimensional composite material MXene@CE obtained by the above preparation method.
[0015] In a specific embodiment, the present invention also provides an application of the hydrogen-bonded multidimensional composite material MXene@CE in the field of CO2 / CH4 mixed gas separation.
[0016] In a specific embodiment, the present invention also provides a mixed matrix membrane, wherein the mixed matrix membrane uses a hydrogen-bonded multidimensional composite material MXene@CE as a filler and a polyether polyimide block Pebax as a polymer matrix, and the filler and the polymer matrix are physically blended at room temperature to form the membrane; the thickness of the mixed matrix membrane is 109 to 132 μm; the mass percentage of the filler in the mixed matrix membrane is 0.5% to 2.0%.
[0017] Furthermore, the present invention also provides the application of the mixed matrix membrane in CO2 capture. Compared with the prior art, the present invention has the following beneficial effects:
[0018] Compared with the prior art, the MXene@CE composite material of the present invention shows significant advantages in gas separation. Traditional two-dimensional materials, such as MXene, have limited transfer of gas molecules in the membrane due to the small interlayer spacing of the nanosheet stacking, resulting in low separation efficiency. However, the present invention successfully increases the interlayer spacing of the MXene nanosheet while providing a polar adsorption environment by introducing polar hydrogen bonding, forming a more spacious gas transfer channel. This innovative design not only improves the gas separation efficiency, but also enhances the stability of the membrane, providing a more competitive solution for efficient CO2 separation.
[0019] In addition, compared with traditional fillers, the MXene@CE composite material of the present invention can overcome the problems of interlayer forces and particle dispersion. Through hydrogen bonding, the MXene@CE filler forms a unique gas transfer path in the membrane, significantly reducing interface defects and transfer resistance. Compared with existing materials, the composite membrane of the present invention has higher CO2 selectivity and permeability, especially in CO2 / CH4 gas separation, showing excellent performance, showing great application potential in the field of energy gas purification. The preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easy to obtain, and the conditions are mild, which can promote the complementary advantages of the filler and the polymer matrix. The research results show that the permeation selectivity of the present invention for CO2 / CH4 mixed gas is up to 530±5Barrer, and the CO2 / CH4 selectivity is 41±1.1. It can reach the Robeson upper limit in 2008. It provides a new and effective strategy for the efficient separation of CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope image of MXene.
[0021] Figure 2 This is the transmission electron microscope image of MXene@CE.
[0022] Figure 3 is a scanning electron microscopy cross-sectional image of the prepared Pebax / MXene@CE-0.5 mixed matrix membrane;
[0023] Figure 4 is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-1.0 mixed matrix membrane;
[0024] Figure 5 is a scanning electron microscopy cross-sectional image of the prepared Pebax / MXene@CE-1.5 mixed matrix membrane;
[0025] Figure 6 is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-2.0 mixed matrix membrane;
[0026] Figure 7 is a scanning electron microscope cross-sectional image of the prepared pure Pebax film. DETAILED DESCRIPTION
[0027] The present invention will be further described below. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Experimental methods without specific conditions in the examples are all based on conventional conditions. The reagents and materials used, unless otherwise specified, can be obtained from commercial channels.
[0028] Example 1
[0029] (1) 1 g of lithium fluoride (LiF) was dispersed in a Teflon beaker containing hydrochloric acid (HCL) (12 mol / L) and 5 mL of deionized water to form suspension A. 1 g of Ti3AlC2 precursor was slowly added to suspension A to form suspension B. Suspension B was stirred at a stirring speed of 500 rpm and reacted at 45-60°C for 2-8 h. After cooling to room temperature, it was centrifuged at a centrifugal speed of 6500 rpm-8000 rpm for 5-10 minutes to obtain suspension C.
[0030] (2) The suspension C prepared in step (1) is placed in a washing bottle for nitrogen protection, and ice bath ultrasound is used for 50 to 150 minutes. The product is collected and repeatedly centrifuged at low temperature at a speed of 3000 rpm to 4000 rpm for 1 to 20 minutes. After repeated washing with hydrochloric acid and deionized water, it is freeze-dried to obtain single-layer or few-layer MXene.
[0031] (3) Add 5 g of cellulose (CE) to 100 mL of deionized water, ultrasonicate for 20 to 30 mins, and stir at a stirring speed of 400 rpm to 500 rpm to obtain a uniformly dispersed suspension D. Mix the product MXene obtained in step (2) and suspension D at a mass ratio of 1:5, stir and ultrasonicate until uniformly dispersed, ultrasonicate for 50 to 80 mins, and stir at a stirring speed of 400 rpm to 500 rpm to form suspension E. Suspension E is placed in a petri dish for freeze drying to obtain MXene@CE.
[0032] Figure 1 Transmission electron microscopy of MXene Figure 2 It is the transmission electron microscopy of MXene@CE; Figure 2It can be seen that MXene@CE presents a morphology of entangled 2D and 1D materials, which further illustrates the ultra-thin characteristics and mixed dimensional structure of MXene@CE. This morphology effectively solves the problem of easy stacking of traditional two-dimensional materials in the membrane. At the same time, by introducing polar hydrogen bonding, the interlayer spacing between MXene nanosheets is expanded, forming a richer CO2 transfer channel. The two-dimensional characteristics of MXene combined with the cellulose structure significantly improve the capture and transfer efficiency of CO2, effectively improve the gas separation performance, and are used to efficiently capture CO2.
[0033] Example 2
[0034] (1) 1 g of lithium fluoride (LiF) was dispersed in a Teflon beaker containing hydrochloric acid (HCL) (12 mol / L) and 5 mL of deionized water to form suspension A. 1 g of Ti3AlC2 precursor was slowly added to suspension A to form suspension B. Suspension B was stirred at a stirring speed of 500 rpm and reacted at 45-60°C for 2 hours. After cooling to room temperature, it was centrifuged at a centrifugal speed of 6500 rpm-8000 rpm for 5-10 minutes to obtain suspension C.
[0035] (2) The suspension C prepared in step (1) is placed in a washing bottle for nitrogen protection, and ice bath ultrasound is used for 50 to 150 minutes. The product is collected and repeatedly centrifuged at low temperature at a speed of 3000 rpm to 4000 rpm for 1 to 20 minutes. After repeated washing with hydrochloric acid and deionized water, it is freeze-dried to obtain single-layer or few-layer MXene.
[0036] (3) Add 5 g of cellulose (CE) to 100 mL of deionized water, ultrasonicate for 20 to 30 mins, and stir at a stirring speed of 400 rpm to 500 rpm to obtain a uniformly dispersed suspension D. Mix the product MXene obtained in step (2) and suspension D at a mass ratio of 1:5, stir and ultrasonicate until uniformly dispersed, ultrasonicate for 50 to 80 mins, and stir at a stirring speed of 400 rpm to 500 rpm to form suspension E. Suspension E is placed in a petri dish for freeze drying to obtain MXene@CE.
[0037] Example 3
[0038] Weigh 0.537g 1657 was dissolved in 10 mL of a mixed solution of ethanol and water with a mass fraction ratio of 7:3, and heated and stirred in a water bath at 80°C for 2 hours to dissolve all the Pebax particles, and a Pebax matrix solution with a mass fraction of 6 wt% was prepared. 0.0028 g of MXene@CE prepared in Example 1 was physically blended with a 6 wt% Pebax matrix solution, and stirred at room temperature for 4 hours to obtain a casting solution, which was poured onto a clean Petri dish for casting; dried at room temperature (25°C) for 48 hours, and then vacuum dried at 40°C in a vacuum drying oven to remove the residual solvent on the surface of the mixed matrix membrane, and a Pebax / MXene@CE-0.5 mixed matrix membrane was obtained, the thickness of which was 118 μm. The weight percentage of MXene@CE in the Pebax / MXene@CE-0.5 mixed matrix membrane was 0.5%, so it was named Pebax / MXene@CE-0.5 mixed matrix membrane.
[0039] Figure 3 The figure is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-0.5 mixed matrix membrane. Figure 3 It can be seen that after the introduction of MXene@CE-0.5 into the Pebax matrix, the cross-section of the mixed matrix membrane becomes rough, which proves that the introduction of filler
[0040] At 25°C and 2 bar, the Pebax / MXene@CE-0.5 mixed matrix membrane was used for the CO2 / CH4 mixed gas separation test. A mixed gas of 80 vol% CH4 and 20 vol% CO2 was used as the raw gas. The dried membrane was moistened with deionized water, and the volume after moistening was about twice the original volume. It was placed in a membrane pool for permeability testing. A circular stainless steel tank was placed in the oven to study the membrane (12.56 cm 2 , center part). In order to test the gas permeability of MMMs under different loads, the feed gas was introduced upstream of the membrane, the flow rate was controlled to be 50mL / min, and the pressure range was 0.2-0.8MPa. In addition, the permeabilities of CO2 and CH4 were calculated based on the sweep gas flow rate and its composition. The effects of H2 back diffusion and concentration polarization on data analysis can be ignored because the volume of the feed gas is much larger than the sweep gas (H2), and the back diffusion of H2 cannot change the composition of the feed gas. Therefore, H2 is suitable as the sweep gas on the downstream side of the membrane, and the flow rate is controlled at 30ml / min. A gas chromatograph (GC 2014C) was used to determine the content of each component in the permeate phase gas. The test results show that its CO2 flux is 425barrer (1barrer=10 -10 cm 3 cm / cm 2 s cmHg), CO2 / CH4 selectivity is 32.
[0041] Example 4
[0042] In this example, 0.0056 g of MXene@CE prepared in Example 1 was physically blended with 6 wt% Pebax matrix solution, stirred at room temperature for 4 h to obtain a casting solution, and the casting solution was poured onto a clean culture dish for casting; dried at room temperature (25°C) for 48 h, and then vacuum dried in a vacuum drying oven at 40°C to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a Pebax / MXene@CE-1.0 mixed matrix membrane, the thickness of which was 126 μm. The weight percentage of MXene@CE in the Pebax / MXene@CE-1.0 mixed matrix membrane was 1%, and was named Pebax / MXene@CE-1.0 mixed matrix membrane.
[0043] Figure 4 The figure is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-1.0 mixed matrix membrane. Figure 4 It can be seen that after MXene@CE is introduced into the Pebax matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. Moreover, MXene@CE is evenly distributed in the mixed matrix membrane without agglomeration. At 25°C and 2 bar, the prepared Pebax / MXene@CE-1.0 mixed matrix membrane was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. The test process was the same as in Example 2. After testing, its CO2 flux was 530 barrer and the CO2 / CH4 selectivity was 41.
[0044] Example 5
[0045] In this example, 0.0083 g of MXene@CE prepared in Example 1 was physically blended with 6 wt% Pebax matrix solution, stirred at room temperature for 4 h to obtain a casting solution, and the casting solution was poured onto a clean petri dish for casting; dried at room temperature (25°C) for 48 h, and then vacuum dried in a vacuum drying oven at 40°C to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a Pebax / MXene@CE mixed matrix membrane with a thickness of 132 μm. The weight percentage of MXene@CE in the Pebax / MXene@CE mixed matrix membrane was 1.5%, and it was named Pebax / MXene@CE-1.5 mixed matrix membrane.
[0046] Figure 5 The figure is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-1.5 mixed matrix membrane. Figure 5It can be seen that after MXene@CE is introduced into the Pebax matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. Moreover, MXene@CE is evenly distributed in the mixed matrix membrane without agglomeration. At 25°C and 2 bar, the prepared Pebax / Pebax / MXene@CE-1.5 mixed matrix membrane was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. Its CO2 flux was 489 barrer, CO2 / CH4 selectivity was 36, and the gas separation performance was greatly improved.
[0047] Example 6
[0048] In this example, 0.0111 g of MXene@CE prepared in Example 1 was physically blended with 6 wt% Pebax matrix solution, stirred at room temperature for 4 h to obtain a casting solution, and the casting solution was poured onto a clean culture dish for casting; dried at room temperature (25°C) for 48 h, and then vacuum dried in a vacuum drying oven at 40°C to remove the residual solvent on the surface of the mixed matrix membrane, to obtain a Pebax / MXene@CE mixed matrix membrane, the thickness of which was 129 μm. The weight percentage of MXene@CE in the Pebax / MXene@CE mixed matrix membrane was 2.0%, and was named Pebax / MXene@CE-2.0 mixed matrix membrane.
[0049] Figure 6 The figure is a scanning electron microscope cross-sectional image of the prepared Pebax / MXene@CE-2.0 mixed matrix membrane. Figure 6 It can be seen that after MXene@CE is introduced into the Pebax matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler. In addition, the filling amount of MXene@CE is too high, resulting in uneven distribution of MXene@CE in the mixed matrix membrane and agglomeration.
[0050] At 25°C and 2 bar, the prepared Pebax / MXene@CE-2.0 mixed matrix membrane was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. Its CO2 flux was 450 barrer and the CO2 / CH4 selectivity was 32.
[0051] Comparative Example 1
[0052] For comparison, 0.537 g of Pebax particles were weighed and dissolved in a mixed solution of 70% ethanol / 30% water by mass. After stirring at 80°C for 2 hours, the resulting casting solution was poured onto a clean ultra-flat surface dish and cast. It was dried at room temperature (25°C) for 48 hours and then placed in a vacuum oven at 40°C for 24 hours to remove the residual solvent, thereby obtaining a Pebax film with a thickness of 109 μm.
[0053] Figure 7 is a scanning electron microscope cross-sectional image of the prepared pure Pebax film. Figure 7 It can be seen that the cross-section of the pure Pebax membrane shows the typical morphology of a smooth, dense and defect-free polymer membrane. At 25°C and 2 bar, the Pebax membrane was used for the separation test of a CO2 / CH4 mixed gas (the volume ratio of CO2 to CH4 is 2:8) with a CO2 volume fraction of 20%. The CO2 flux was tested to be 280 barrer and the CO2 / CH4 selectivity was 24. Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogen-bonded multidimensional composite material MXene@CE, characterized in that: The preparation method comprises the following steps: (1) Lithium fluoride (LiF) is dispersed in a Teflon beaker containing hydrochloric acid (HCL) and deionized water to form a suspension A. Ti3AlC2 precursor is slowly added to the suspension A to form a suspension B. The suspension B is stirred and reacted under heating conditions, cooled to room temperature and centrifuged to obtain a suspension C. (2) The suspension C prepared in step (1) is placed in a washing bottle for nitrogen protection. After ice bath ultrasound, the product is collected and centrifuged at low temperature. After repeated washing with hydrochloric acid and deionized water, it is freeze-dried to obtain single-layer and few-layer MXene. (3) Add cellulose (CE) to deionized water, sonicate and stir to obtain a uniformly dispersed suspension D. Mix step (2) and suspension D in proportion, stir and sonicate until uniformly dispersed to form suspension E. Place suspension E in a petri dish and freeze-dry to obtain MXene@CE.
2. The preparation method according to claim 1, characterized in that: (1) The amount of lithium fluoride (LiF), hydrochloric acid (HCl) and deionized water described in step (1) is: 1g: 15mL: 5mL; the amount of the Ti3AlC2 precursor and the suspension A is 1g: 20mL, and the suspension B is a reaction system composed of lithium fluoride and hydrochloric acid solution. The suspension B is heated and stirred, the stirring speed is 500-800rpm, the stirring temperature is 45-60°C, the reaction time is 2-8h, and after cooling to room temperature, centrifugation is performed, the centrifugation speed is 6500-8000rpm, and the centrifugation time is 5-10mins, to obtain suspension C. (2) The nitrogen protection condition described in step (2) is: transferring the suspension C to a washing bottle, performing low-temperature ultrasonic treatment under nitrogen protection, wherein the ultrasonic temperature is 0°C to 10°C, and the ultrasonic treatment time is 50 to 150 mins; after ultrasonication, repeatedly centrifuging at low temperature, wherein the centrifugal speed is 3000 to 4000 rpm, and the time is 1 to 20 mins, repeatedly washing with deionized water and hydrochloric acid until the pH is > 6, and then freeze-drying for 24 to 48 hours to obtain a single layer or a few layers of MXene. (3) The amount of cellulose (CE) in step (3) is 5 g, the amount of deionized water is 100 mL, the cellulose is dissolved and ultrasonically treated, the ultrasonic time is 20 to 30 mins, the stirring speed is 400 rpm to 500 rpm, and a uniformly dispersed suspension D is obtained. The mixing ratio of the MXene product and the cellulose suspension D in step (2) is 1:
5. After mixing, the mixture is stirred and ultrasonically treated, the ultrasonic time is 50 to 80 mins, and the stirring speed is 400 rpm to 500 rpm, until the mixture is uniformly dispersed to form a suspension E. The suspension E is placed in a culture dish and freeze-dried for 24 to 48 hours to obtain a MXene@CE composite material.
3. Application of the hydrogen-bonded multidimensional composite material MXene@CE according to claim 1 in the field of CO2 / CH4 mixed gas separation.
4. A mixed matrix membrane, wherein the mixed matrix membrane uses MXene@CE as a filler and polyether polyamide block Pebax as a base material, and the filler and the base material are physically blended at room temperature; the thickness of the mixed matrix membrane is 109 to 132 μm; the mass percentage of the filler in the mixed matrix membrane is 0.5% to 2.0%.
5. Use of the mixed matrix membrane according to claim 4 in CO2 capture.